Tree diversity and carbon stocks in the Itombwe Mountains of eastern DR Congo. (1st August 2021) - Imani, Gérard; Kalume, John; Marchant, Rob; Calders, Kim; Batumike, Rodrigue; Bulonvu, Franklin; Cuni‐Sanchez, Aida
Abstract: Our ecological understanding of tropical montane forests in Africa is still limited, particularly in the Albertine Rift. Because of a greater role of environmental filtering at higher elevations, tree species' richness and aboveground biomass (AGB) is expected to decrease with increasing elevation. However, broader scale patterns are complex and different patterns have also been observed in different mountains. We established eight permanent 1‐ha plots in Itombwe Mountains and sampled all trees ≥10 cm diameter following standard RAINFOR protocols to investigate tree species' richness, forest structure, and estimated AGB. We also collected and analyzed soil samples to establish how these affected AGB. We identified over 120 tree species, 12 of which were of international conservation concern according to IUCN criteria. Species richness was significantly negatively correlated with elevation. AGB ranged from 268 Mg/ha (submontane) to 396 Mg/ha (middle montane forests), and it was significantly positively correlated with elevation, soil organic matter, and soil organic C and N. We compare Itombwe with other montane forests in the Albertine Rift, to demonstrate their high floristic diversity, high abundance of large stems, and high AGB, insights which are crucial for the future management of these unique forests. Abstract in French is available with online material. Abstract : Our ecological understanding of tropical montane forests in Africa is still limited, particularly in the Albertine Rift species' richness and aboveground biomass (AGB) is expected to decrease with increasing elevation AGB ranged from 268 Mg/ha (submontane) to 396 Mg/ha (middle montane forests) and it was significantly positively correlated with elevation, soil organic matter, and soil organic C and N. RESUMÉ: Notre compréhension de l'écologie de forêts tropicales de montagne en Afrique est encore limitée, en particulier dans le Rift Albertin. En raison du rôle plus important du filtrage environnemental à des altitudes plus élevées, la richesse en espèces d'arbres et la quantité de biomasse aérienne (AGB) devraient diminuer avec l'augmentation de l'altitude. Cependant, les modèles généralistes sont complexes raison pour laquelle différents modèles ont été proposés dans différentes montagnes. On a installé huit parcelles permanentes de 1 ha chacune dans les montagnes d'Itombwe et échantillonné tous les arbres de diamètre ≥10 cm selon les protocoles standard de RAINFOR afin d'étudier la richesse en espèces, la structure de la forêt et estimer la biomasse. On a également collecté et analysé les échantillons du sol pour déterminer comment les caractéristiques adaphiques impactent sur l'AGB. On a identifié plus de 120 espèces d'arbres, dont 12 étaient listées préoccupantes selon les critères de la conservation internationale de l'UICN. La richesse spécifique était négativement corrélée avec l'altitude significativement. L'AGB variait entre 268 Mg/ha (sous‐montagnards) et 396 Mg/ha (forêts de moyenne montagne). L'AGB était positivement corrélée avec l'altitude, la matière organique, le C et le N organiques du sol significativement. On a comparé Itombwe avec d'autres forêts de montagne dans le Albertine Rift, pour démontrer sa spécifique en termes de grande diversité floristique, d'abondance en gros arbres et de la biomasse importante et qui sont les informations cruciales pour la gestion future de ces forêts uniques.